Analysis of Malachite Green, Gentian Violet and Their Leuco Metabolites in Catfish and Carp by Micellar Electrokinetic Capillary Chromatography - 姜廷福(Ting-Fu Jiang); 呂志華(Zhi-Hua Lv); 王遠紅(Yuan-Hong Wang) (Yàowu shi͡p︡in fenxi, 2012)
A simple, reproducible and sensitive micellar electrokinetic chromatography (MEKC) method was developed for the separation and determination of malachite green (MG). leucomalachite green (LMG), gentian violet (GV) and leucogentian violet (LGV) from catfish and carp. Field-enhanced sample injection with reverse migrating micelles (FESI-RMM) was used for on -line concentration of the analytes. The buffer contained 50 mM H3PO4-NaOH, 140 mM sodium dodecyl sulfate (SDS), 15% acetonitrile and 15% 2-propanol, at the pH of 2.0. The sample solution was diluted with water containing 5 mM SDS and injected for 15 s with -8 kV after injection of 92 s water plug. The effects of concentration of SDS and organic modifier, the sample matrix, the injection time of water plug, the injection voltage and injection time of sample on the separation and stacking efficiency were investigated. Under the optimum conditions, the analyzes were well separated and by optimizing the stacking conditions, about 121, 146, 150 and 87 fold impro